1982
DOI: 10.1055/s-2007-1019076
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate Intoxication and Glucose-Induced Insulin Secretion in the Rat

Abstract: The hypoglycemic salicylate action has been related to an increased insulin secretion (Micossi, Pontiroli, Baron, Tamayo, Lengel, Bevilacqua, Raggi, Norbiato and Foa 1978). In this report we describe the effects of salicylate on the dynamics of glucose-induced insulin secretion, in the isolated perfused rat pancreas. Material and MethodsMale Wistar rats, weighing 200-300 g, were used, and in all cases were fasted overnight prior to each perfusion. Sodium salicylate 50 mg/100 g of body weight was injected subcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Since in normal man treatment with other inhibitors of PG synthesis, such as ibuprofen [5] or indomethacin [7,8], is associated with unaltered or decreased insulin responsiveness to glucose, respectively, it may be assumed that the different effects of these drugs may be due to actions apart from inhibiting PG synthesis. As to experiments in vitro, sodium salicylate has been shown to augment glucose-induced insulin release by the isolated perfused rat pancreas [22], and by monolayer cultures of rat pancreatic cells [23], but not by hamster islets [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since in normal man treatment with other inhibitors of PG synthesis, such as ibuprofen [5] or indomethacin [7,8], is associated with unaltered or decreased insulin responsiveness to glucose, respectively, it may be assumed that the different effects of these drugs may be due to actions apart from inhibiting PG synthesis. As to experiments in vitro, sodium salicylate has been shown to augment glucose-induced insulin release by the isolated perfused rat pancreas [22], and by monolayer cultures of rat pancreatic cells [23], but not by hamster islets [24].…”
Section: Discussionmentioning
confidence: 99%
“…An effect on plasma insulin is not seen, when indomethacin or ibuprofen [5] is employed instead of ASA. Although a great deal of in-vitro data directly demonstrate that ASA along with other inhibitors of PG synthesis stimulate insulin secretion [22,23], species differences may exist [24] and invitro experiments may not accurately reflect hormonal events in intact man. Several studies have demonstrated that salicylate or ASA lower plasma glucose in normal subjects [191 and Type 2 diabetic patients [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes 36:1047-53,1987 P rostaglandin E 2 (PGE 2 ) inhibits glucose-induced insulin secretion in humans, animals, and some in vitro pancreatic islet preparations (1)(2)(3)(4)(5)(6). Inhibitors of PGE 2 synthesis augment glucose-induced insulin secretion both in vivo (1,2,7,8) and in vitro (9)(10)(11)(12) and partially restore defective insulin secretion in type II diabetic patients (1,8,13). Despite the reproducible nature of these findings, confusion exists regarding prostaglandin regulation of insulin secretion.…”
Section: Sulfate-polyacrylamide Gels Revealed Adp-ribosylation Of a Cmentioning
confidence: 95%
“…Experiments with cyclooxygenase inhibitors also yielded disparate results, suggesting inhibition, stimulation or lack of an effect by endogenous PGs on insulin release (7,(10)(11)(12)(13).…”
mentioning
confidence: 99%